Secondary angle closure glaucoma by lupus choroidopathy as an initial presentation of systemic lupus erythematosus: a case report. Issue 1 (December 2015) - Han, Young; min Yang, Chan; Lee, Sang-Hoon; Shin, Jae; Moon, Sang; Kang, Ja
Abstract Background We present a rare case of secondary angle closure glaucoma due to systemic lupus erythematosus choroidopathy as initial presentation of systemic lupus erythematosus, accompanied by central nervous system vasculitis and uncontrolled nephropathy. Case presentation A 31-year-old woman presented with decreased visual acuity, nausea, vomiting, fever, and bilateral angioedema-like eyelid swelling. She had persistent dry cough while taking medication for 3 months, and had usual posterior neck pain, which was treated with analgesic medication and Asian medicines. Intraocular pressure was 32 and 34 mmHg in her right and left eyes, respectively. Peripheral anterior chambers were shallow (grade I) using the van Herick method. Gonioscopy revealed 360° closed angle in both eyes. In both eyes, serous retinal detachment was found using optical coherence tomography and B scan ultrasonography, as well as choroidal thickening with effusion. Secondary acute angle closure glaucoma was drug induced, or caused by uveitis of unknown etiology when she was first treated with intraocular pressure-lowering medication. During evaluation of the drug-induced angioedema in the internal medicine department, systemic lupus erythematosus was diagnosed, based on malar rash, photosensitivity, proteinuria, and positive anti-Smith and anti-DNA antibodies, followed by initiation of steroid pulse therapy. Using fluorescein angiography, multifocal subretinal pinpoint foci were detected at the middle phase. We then diagnosed bilateral angle closure glaucoma by choroidal effusions, with lupus choroidopathy. At 2 months after steroid pulse therapy, subretinal fluid was not found, and visual acuity improved to normal. During the subsequent 2 years, lupus choroidopathy was not aggravated but lupus nephritis was not controlled. Conclusion Patients with systemic lupus erythematosus choroidopathy can develop ciliochoroidal effusion, which can lead to acute angle closure glaucoma. Systemic lupus erythematosus choroidopathy is an early sign of severe complications. Angle closure glaucoma by systemic lupus erythematosus choroidopathy can be effectively treated using antiglaucoma drugs and immunosuppressive therapy.